Evaluación a escala de laboratorio del desempeño de una lechada de cementación utilizando nano-zeolita (2020)
Based on API 10B, a methodology for the development of this research was structured for the evaluation of Nano-zeolite on the properties of the base cementation grout. Determining that the best evaluated scenario is in which 3% Nano-zeolite was added to the cementation slurry, because in this the greatest benefits for cementation grout were demonstrated, seeing significant increases in resistance to compressive strength over time, and the decrease in time that cementing slurry needs to achieve resistance of 50 psi, 500 psi and 2000 psi, in addition, a direct relationship between the percentage of Nano-zeolite used, the increase in compressive strength over time and in the early development of compressive strength.